The Efficacy of Intra-Arterial Plus Intravesical Chemotherapy Versus Intravesical Chemotherapy Alone After Bladder-Sparing Surgery in High-Risk Bladder Cancer: A Systematic Review and Meta-Analysis of Comparative Study - Zhou, Zhongbao; Cui, Yuanshan; Huang, Shuangfeng; Chen, Zhipeng; Zhang, Yong (Frontiers in Oncology, 2021)
Background Due to the poor prognosis, the treatment of high-risk bladder cancer (HRBC) remains controversial. This meta-analysis aims to access the efficacy of intra-arterial chemotherapy (IAC) combined with intravesical chemotherapy (IC) versus IC alone after bladder-sparing surgery in HRBC. Methods A systematic search of PubMed, Cochrane Library databases, EMBASE (until June 2020) was conducted. PRISMA checklist was followed. The data were analyzed by RevMan v5.3.0. Results A total of five articles including 843 patients were studied. The analysis demonstrated that the IAC + IC group had a greater improvement of overall survival (P = 0.02) and significant reduction in terms of tumor recurrence rate (P = 0.0006) and tumor progression rate (P = 0.008) compared with the IC group. The recurrence-free survival in the IAC + IC group was significantly higher than that in the IC group (P = 0.004), but there was no significant difference in progression-free survival between the two groups (P = 0.32). In addition, the combination of IAC and IC significantly extended tumor recurrence interval (P = 0.0001) and reduced tumor-specific death rate (P = 0.01) for patients with HRBC compared with IC alone. For side effects related with IAC, although about half of the patients experienced some toxicities, most of them were mild and reversible (grades 1–2, 22.3% vs. grade 3–4, 2.7%), mainly including nausea/vomiting (P = 0.0001), neutropenia (P = 0.002), and alanine aminotransferase (P = 0.0001). Conclusion Patients with HRBC treated with IAC + IC after bladder-sparing surgery had a marked improvement in the overall survival, recurrence-free survival, time interval to first recurrence, tumor recurrence rate, tumor progression rate, and tumor-specific death rate than patients treated with IC alone. However, progression-free survival was not significantly correlated with treatment strategy. In addition, patients seemed to tolerate well the toxicities related with IAC. Systematic Review Registration PROSPERO, identifier CRD42021232679.